Ten years that shook the media world: big questions and big trends in international media developments - Kleis Nielsen, R (Reuters Institute for the Study of Journalism, 2012)
This report documents some very significant differences in how media companies in different countries have fared over the last decade, examining six affluent democracies (Finland, France, Germany, Italy, the United Kingdom and the United States) as well as two emerging economies (Brazil and India).